INTERNALIZATION OF RELIGIOUS VALUES THROUGH SOCIAL INTERACTION OF SMKN 1 KLATEN STUDENTS - Alfina Tri Oktafiana; Nurul Latifatul Inayati (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
This research was conducted in order to find out how teachers implement Islamic values in students at SMK N 1 Klaten. This research aims to find out what methods are used to implement values in school activities at SMK N 1 Klaten. This research study uses a qualitative descriptive method. This research is included in the classification of field research carried out at SMK N 1 Klaten. The data obtained from this research is through observations, interviews, and documentation from school principals, PAI teachers, and students of SMK N 1 Klaten. The results of this research show that there are several methods for implementing Islamic values carried out at SMK N 1 Klaten, including the habit of reading the Al-Qur'an before learning, dhuha prayers in congregation, and students' religious activity sheets. In the implementation of school activities there are also supporting and inhibiting factors. Supporting factors include support from parents/guardians and from the school. Meanwhile, the inhibiting factors come from the students' different backgrounds. Based on the results of research regarding the implementation of Islamic religious values at SMK N 1 Klaten using the habituation method in school activities, including reading the Al-Qur'an before the first lesson begins, praying Dhuha in congregation, and religious activity sheets for students, The implementation of several of these habits is carried out according to each habit and is carried out at any time in everyday life. In implementing this habituation, supporting and inhibiting factors arise. Supporting factors include support from parents and guardians as well as from the school, which always controls students to always implement Islamic religious values. Meanwhile, the inhibiting factors include students' different backgrounds in reading the Al-Qur'an, but teachers at SMK N 1 Klaten have a solution to this by directing students to take part in the BTA extracurricular.